Black Garlic Antioxidant Activity Test (Allium Sativum) Compound Types with DPPH Method (1,1-Difenil-2-Pikrilhidrazil) - Asih, Sari Wulan; Nurseta, Tatit; Kusworini, Kusworini; Yudhanto, Hendy Setyo (JURNAL INFO KESEHATAN, 2024)
Antioxidants are needed to neutralize Reactive Oxygen Species (ROS) in the body and prevent cardiovascular, cancer, and premature aging as degenerative diseases. Antioxidants will provide resistance to free radicals and prevent damage in normal cells, proteins, and fats, and are able to break chain reactions without disrupting their function. Black Garlic has higher antioxidant properties than regular garlic. S-allyl cysteine (SAC) is a compound from Black Garlic that functions as an antioxidant that can affect the cell cycle in apoptosis, which can provide cell protection from free radical damage. In a study, it was said that a single type of Black Garlic extract obtained IC50 52.055 ppm (µg/mL) which is included in the category of high antioxidant activity. While in the antioxidant activity test, this study used a compound type of black garlic on the grounds that the price is more affordable and easy to find in traditional markets. This study aims to evaluate the potential of compound-type black garlic extract against free radicals by testing antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results of the compound type Black Garlic antioxidant test stated to have an IC50 value of 173 ppm (µg/mL) which is classified as moderate antioxidant activity. So researchers assume that the use of single type Black Garlic extract is more effective than compound type Black Garlic.